Characterization preliminary breakdown in the measured lightning electric fields on Malaysia data - Arshad, S. N. M.; Abd. kadir, Mohd. Zainal Abidin; Izadi, Mahdi; Ariffen, A. M.; Hamzah, M. N.; Gomes, Chandima; Jasni, J.; Rameli, N. (Scientific.Net, 2015)
This paper presents a characteristic of lightning electric fields. The lightning electric fields were captured by two parallel plats sensor and the characterization for preliminary breakdown pulse (PBP) was studied. A total of 207 data were recorded and 10 data are selected and been utilized in this paper accordingly. In PBP signal data, time before return stroke, ending time and maximum peak of PBP were analyzed. The time duration between the PBP and the occurrence of return stroke was obtained as 0.64 ms and 4.05 ms and then compared with results from other researchers.